Ictal Mammalian Dive Response: A Likely Cause of Sudden Unexpected Death in Epilepsy - Vega, Jose L. (Frontiers in Neurology, 2018)
Even though sudden unexpected death in epilepsy (SUDEP) takes the lives of thousands of otherwise healthy epilepsy patients every year, the physiopathology associated with this condition remains unexplained. This article explores important parallels, which exist between the clinical observations and pathological responses associated with SUDEP, and the pathological responses that can develop when a set of autonomic reflexes known as the mammalian dive response (MDR) is deployed. Mostly unknown by physicians, this evolutionarily conserved physiological response to prolonged apnea economizes oxygen for preferential use by the brain. However, the drastic cardiovascular adjustments required for its execution, which include severe bradycardia and the sequestration of a significant portion of the total blood volume inside the cardiopulmonary vasculature, can result in many of the same pathological responses associated with SUDEP. Thus, this article advances the hypothesis that prolonged apneic generalized tonic clonic seizures induce augmented forms of the MDR, which, in the most severe cases, cause SUDEP.